2015
DOI: 10.17116/neiro201579629-37
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of SDR in various groups of cerebral palsy (CP) patients

Abstract: A reduction in spasticity due to SDR depends on the amount of cut roots. The functional result of SDR is affected not only by a decrease in spasticity but also by the functional status and age of the patient at the time of surgery. In all cases, laminoplasty should be performed to prevent spinal cord deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Age of cases at SDR was found to be highly correlated with the changes of GDI in our retrospective statistical analysis, which was similar to the ndings in previous studies 10,26 . Such results might be attributed to the adaptability of gait training, of which younger cases usually have better plasticity for motor control 27,28 . In the meantime, we found that the improvements of GDI are more likely to appear after 6-month post-op rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…Age of cases at SDR was found to be highly correlated with the changes of GDI in our retrospective statistical analysis, which was similar to the ndings in previous studies 10,26 . Such results might be attributed to the adaptability of gait training, of which younger cases usually have better plasticity for motor control 27,28 . In the meantime, we found that the improvements of GDI are more likely to appear after 6-month post-op rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…Cobb et al [45] suggested that that laminoplasty instead of laminectomy may prevent the development of lumbar musculoskeletal pain after SDR. Dekopov et al [46] evaluated 10 year outcomes of SDR in those with CP; they concluded that the degree of spasticity reduction due to SDR is directly dependent on the number of cut roots. The functional result of SDR is affected not only by a decrease in spasticity but also by the functional status and age of the patient at the time of surgery.…”
Section: Technical Advancementsmentioning
confidence: 99%